Doing the minimum required : a review of Human Rights Education in Icelandic compulsory schools - Ársól Clara Arnardóttir 2000- (2022)
My motivation for this paper comes from my own experience with Human Rights Education (HRE). This paper seeks to explore how HRE is understood and implemented in an Icelandic compulsory school. I talk to two teachers to draw on their perspectives and later conduct a review of education, laws and policies related to human rights in Iceland. The results of my analysis of these two data sets show that education on human rights is left to individual teachers. Despite human rights appearing as one of the six fundamental pillars in the national curriculum guides, the absence of a national human rights institution in Iceland to carry out independent evaluations of HRE means that HRE implementation in schools lacks a comprehensive and systematic approach. This paper concludes by recommending that further research be conducted on HRE in the Icelandic school system to ensure that human rights rhetoric becomes a reality in practice.